Nephrotic syndrome in children during the COVID-19 pandemic - Maniar, Aesha; Cocorpus, Jenelle; Basalely, Abby; Castellanos, Laura; Singer, Pamela; Sethna, Christine B (Journal of Clinical Nephrology, 2022)
The COVID-19 pandemic resulted in public health measures and fewer viral infections, which trigger the nephrotic syndrome. Our objectives were to characterize the effect of the COVID-19 pandemic on children with nephrotic syndrome. This single-center retrospective chart review compared children with nephrotic syndrome one year before the pandemic with the first wave of the pandemic. Epidemiologic events, clinical characteristics, and health care utilization were compared using paired t-tests, Fisher’s exact tests and Wilcoxon Rank Sum tests. Among 96 children the mean age was 10.7 ± 5.28 years. The distribution was minimal change disease (16.7%), focal segmental glomerulosclerosis (12.5%), membranous nephropathy (1%) and not biopsied (69.8%). Medication responsiveness was steroid-sensitive (25%), frequently relapsed (54%) and steroid-resistant (20.8%). There were 14 new diagnoses of nephrotic syndrome pre-pandemic and 18 during the pandemic. Fewer relapses during the pandemic were likely due to fewer viral illnesses from public health measures during the pandemic.